2013
DOI: 10.1159/000355523
|View full text |Cite
|
Sign up to set email alerts
|

Oral Intake of Specific Bioactive Collagen Peptides Reduces Skin Wrinkles and Increases Dermal Matrix Synthesis

Abstract: Dietary consumption of food supplements has been found to modulate skin functions and can therefore be useful in the treatment of skin aging. However, there is only a limited number of clinical studies supporting these claims. In this double-blind, placebo-controlled study, the effectiveness of the specific bioactive collagen peptide (BCP) VERISOL® on eye wrinkle formation and stimulation of procollagen I, elastin and fibrillin biosynthesis in the skin was assessed. A hundred and fourteen women aged 45-65 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
121
1
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(140 citation statements)
references
References 18 publications
5
121
1
13
Order By: Relevance
“…DNA microarray technology makes it possible to analyze comprehensively the expression of many genes and to find several novel markers associated with physiological functions. It is an effective approach to understand how food ingredients affect gene expression in target tissues (11,24).Although some studies described the effect of collagen hydrolysate administration on the skin (27,37,55), there is no description or comprehensive analysis of how long-term administration of collagen hydrolysate affects gene expression associated with skin barrier function and elasticity under conditions of intrinsic aging. The mechanism of improvement of aged skin function remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DNA microarray technology makes it possible to analyze comprehensively the expression of many genes and to find several novel markers associated with physiological functions. It is an effective approach to understand how food ingredients affect gene expression in target tissues (11,24).Although some studies described the effect of collagen hydrolysate administration on the skin (27,37,55), there is no description or comprehensive analysis of how long-term administration of collagen hydrolysate affects gene expression associated with skin barrier function and elasticity under conditions of intrinsic aging. The mechanism of improvement of aged skin function remains unclear.…”
mentioning
confidence: 99%
“…Although some studies described the effect of collagen hydrolysate administration on the skin (27,37,55), there is no description or comprehensive analysis of how long-term administration of collagen hydrolysate affects gene expression associated with skin barrier function and elasticity under conditions of intrinsic aging. The mechanism of improvement of aged skin function remains unclear.…”
mentioning
confidence: 99%
“…We hypothesize that this increase may be due to the dual action mechanism of collagen bioactive peptides in the dermis: (1) free amino acids provide support for the formation of collagen fibers [34] ; (2) bioactive peptides bind to fibroblasts membrane receptors and stimulate their proliferation [35] and the production of new collagen [33,36,37] , elastin [33] , and hyaluronic acid [29] .…”
Section: Discussionmentioning
confidence: 99%
“…The oral intake of collagen bioactive peptides instead, due to their low molecular weight, permits a systemic absorption and distribution of these peptides in the different tissues [27,28,32] . Collagen peptides activate fibroblasts, leading to the production of collagen [33] , elastin [33] and hyaluronic acid [29] .…”
Section: Introductionmentioning
confidence: 99%
“…Collagen peptides have been reported to have numerous distinct bioactivities, including anti-oxidization, anti-aging, promoting the repair and growth of corneal epithelial cells, promoting the metabolism of skin collagen, immunomodulation, et al [7,8].The bioactivity of collagen is directly correlated to its molecular weight. Han and colleagues found that the Halibut skin collagen peptides (600-1,800Da) could inhibit angiotensin I-converting enzyme activity in a molecular weight-dependent manner; low molecular weight collagens are more potent inhibitors for angiotensin I-converting enzyme [9].…”
Section: Discussionmentioning
confidence: 99%